2021
DOI: 10.21203/rs.3.rs-407029/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paraquat Modulates Immunological Function in Bone Marrow-Derived Macrophages

Abstract: Paraquat (PQ) is an herbicide commonly used worldwide. This herbicide is known to alter the human and animal immune systems. Many reports indicated that PQ impacts immune cell viability and functions. However, the underlying mechanism critical is still unknown. Therefore, the aim of this study was to evaluate effects of PQ on free radical production, oxidative stress, cell death, and pro-inflammatory gene expression of murine bone marrow-derived macrophages (BMDMs) from female C57BL/6NJcl mice in vitro. BMDMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Effects are also in expose-time and PQconcentration dependent manners. The results further confirm our previous study that PQ increased the cytotoxicity of bone marrow-derived macrophages [14] and the previous report that PQ decreased human neural progenitor cells [15].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Effects are also in expose-time and PQconcentration dependent manners. The results further confirm our previous study that PQ increased the cytotoxicity of bone marrow-derived macrophages [14] and the previous report that PQ decreased human neural progenitor cells [15].…”
Section: Resultssupporting
confidence: 92%
“…Apoptosis constitutes one of the major mechanisms underlying pathological characterized caused by PQ [5]. We have previously shown that PQ caused apoptosis in macrophages [14]. To further elucidate the effects of ML extracts in PQ-induced apoptosis, thus cell apoptosis was subsequently performed.…”
Section: Effect Of Pq On Apoptosis Of Raw 2647 Macrophages After Pre-...mentioning
confidence: 99%
“…MDA levels in the cell culture supernatants were determined after 48 h of LPS exposure using a thiobarbituric acid reactive substance assay described by Srinontong et al . [ 21 ]. Briefly, aliquots of the reaction mixture containing cell supernatant, 0.12 M thiobarbituric acid, 0.9% NaCl, and 10% trichloroacetic acid were heated at 100°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%